Experience of the Tocilizumab Application in Systemic Onset Juvenile Arthritis - A. V. Krasnopol’skaja; O. N. Soldatova; E. S. Samoshkina; N. V. Shekina; L. A. Balykova (Вопросы современной педиатрии, 2015)
The article provides information on the unfavourable course of systemic onset juvenile arthritis, resistant to immunosuppressive therapy with methotrexate in combination with cyclosporine, and pulse therapy with methylprednisolone and methotrexate. We describe the successful use of genetically engineered biological drug tocilizumab in the patient with systemic onset juvenile arthritis. After the first injection, pain was already significantly reduced; after the second, fever was relieved and non-steroid anti-inflammatory drugs were cancelled; after the third, lymphadenopathy and splenomegaly disappeared and the child’s functional activity improved significantly. After 12 months of treatment, an inactive phase of the disease was achieved, the joints’ kinetics (with the exception of the right hip) were almost entirely restored and the patient’s quality of life had significantly improved. At the same time, metabolic disorders and changes in the cardiovascular system were reversed. This example demonstrated the high effectiveness of interleukin-6 antagonist tocilizumab in systemic arthritis, which allowed arresting joint affection as well as extra-articular manifestations of the disease, providing normal puberty, the restoration of growth and sexual development.